Transcultural adaptation and validation of the patient empowerment in long-term conditions questionnaire - Paloma Garcimartin; Josep Comin-Colet; Pilar Delgado-Hito; Neus Badosa-Marcé; Anna Linas-Alonso (BMC, 2017)
Abstract Background Patient empowerment is a key element to improve the results in health, increase satisfaction amongst users and obtain higher treatment compliance. The main objective of this study is to validate the Spanish version of the questionnaire "Patient empowerment in long-term conditions" which evaluates the patients' level of empowerment of chronic diseases. The secondary objective is to identify factors which predict basal empowerment and changes (improvement or deterioration) in patients with Heart Failure (HF). Methods An observational and prospective design of psychometric type to validate a questionnaire (aim 1) and a prospective study of cohorts (aim 2). The study will include 121 patients with confirmed diagnosis of HF. Three measurements (basal, at 15 days and at 3 months) will be carried out: quality of life, self-care and empowerment. Descriptive and inferential analyses will be used. For the first aim of the study (validation), the test-retest reproducibility will be assessed through intraclass correlation coefficient; internal consistency will be assessed through Cronbach's alpha coefficient; construct validity through Pearson's correlation coefficient; and sensibility to change through effect size coefficient. Discussion Set a valid questionnaire to measure the level of empowerment of patients with chronic diseases could be an effective tool to assess the results from the provision of the health care services. It will also allow us to identify at an early stage, those groups of patients with a low level of empowerment. Hence, they could become a risk group due to poor management of the disease, with a high rate of decompensation and a higher use rate of the health system resources.